High-strength environment-friendly plastic and preparation method thereof
By grafting PLA with chitosan PVC and combining appropriate compatibilizers and fillers, the shortcomings of traditional PVC materials in terms of strength and environmental protection are solved, and a new plastic material with high strength and environmental protection are achieved.
Patent Information
- Application Number
- CN202411673666.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional PVC materials have shortcomings in strength and environmental protection, limiting their use in high-strength applications and may involve plasticizers and stabilizers that are potentially harmful to the environment and health during production.
Material formulations are optimized to improve material performance by combining polylactic acid (PLA) with chitosan-grafted polyvinyl chloride (PVC) with appropriate compatibilizers and fillers. Specific methods include plasma treatment, grafting reaction, ultrasonic assisted dispersion and other technical means.
It significantly improves the toughness and stability of the material, increases the biodegradation and antibacterial properties, and improves the strength and impact resistance of the material by modifying nano calcium carbonate.
Smart Images

Figure BDA0005146526610000121 
Figure BDA0005146526610000131
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polyvinyl chloride materials and relates to a high-strength environmentally friendly plastic and a preparation method thereof. Background Art
[0002] Polyvinyl chloride (PVC) is a widely used plastic material that is favored in many fields for its good processing performance and economy. However, traditional PVC materials have certain shortcomings in terms of strength and environmental protection. Generally speaking, PVC has low strength and toughness, which limits its use in certain high-strength applications. In addition, the traditional PVC production process may involve the use of plasticizers and stabilizers that are potentially harmful to the environment and health, which makes its environmental protection questionable.
[0003] In the field of toy manufacturing, PVC materials are widely used because of their easy processing, low cost and good plasticity. The design of toys usually requires complex shapes and various colors, which makes PVC an ideal choice. However, as consumers' requirements for safety and environmental protection continue to increase, the shortcomings of traditional PVC materials in these aspects are gradually revealed. In addition, PVC is also widely used in pipes and profiles in building materials, interior parts such as dashboards and door panels in the automotive industry, infusion tubes and blood bags for medical devices, and other products.
[0004] The present invention successfully develops a high-strength environmentally friendly plastic by compounding polylactic acid (PLA) with PVC and combining appropriate compatibilizers and fillers. This new material not only has significantly improved mechanical properties, but also reduces the impact on the environment during the production process. The material performance is improved by optimizing the material formula, making it more suitable for use in products such as toys that have high requirements for safety and durability. Summary of the invention
[0005] The present invention relates to a high-strength environmentally friendly plastic and a preparation method thereof, and belongs to the technical field of polyvinyl chloride materials. The present invention uses chitosan grafted polyvinyl chloride and polylactic acid as raw materials, adds environmentally friendly and safe compatibilizers and thermal stabilizers for blending, which not only improves the toughness and stability of the material, but also increases the biodegradability and antibacterial properties of the chitosan grafted polyvinyl chloride; nano calcium carbonate is modified by polyacrylic acid, stearic acid and silane coupling agent, effectively improving the dispersion and combination of inorganic calcium carbonate in the polymer, and further increasing the strength of the material.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A high-strength environmentally friendly plastic, characterized by comprising the following raw materials in parts by weight: 20-30 parts by weight of modified PVC, 20-30 parts by weight of PLA, 2.5-10 parts by weight of a compatibilizer, 6-10 parts by weight of a filler and 3-4 parts by weight of a heat stabilizer.
[0008] As a preferred technical solution of the present invention, the modified PVC is chitosan-grafted PVC, and the preparation method is: placing the PVC in a plasma reaction chamber for plasma treatment for 20-40 minutes to introduce carboxyl groups on the surface of the PVC; immersing it in an N-hydroxysuccinimide aqueous solution for treatment for 0.5-1 hour to form an activated ester intermediate, immersing the activated ester intermediate in a chitosan solution for 2-8 hours for grafting, washing it with deionized water, and then drying it to obtain the chitosan-grafted PVC.
[0009] As a preferred technical solution of the present invention, the plasma treatment uses 95%-99% helium and 1%-5% oxygen as blocking media, the voltage is 3-8KV, the frequency is 30-50KHz, the duty cycle is 25%-55%, and the modulation frequency is 80-120Hz; the concentration of the N-hydroxysuccinimide aqueous solution is 0.1-0.2M; the chitosan solution is a chitosan acetic acid solution, the acetic acid concentration is 1-2% (V / V), and the chitosan concentration is 1-2% (m / m).
[0010] As a preferred technical solution of the present invention, the compatibilizer is any one of epoxidized soybean oil, maleic anhydride grafted polyethylene, and maleic anhydride grafted polypropylene.
[0011] As a preferred technical solution of the present invention, the filler is modified nano calcium carbonate, and the preparation method is as follows: adding nano calcium carbonate to a polyacrylic acid solution, stirring evenly and using ultrasonic assisted dispersion treatment for 20-30 minutes, washing and drying to obtain nano calcium carbonate A; dissolving stearic acid in anhydrous ethanol to form a stearic acid solution, then dispersing nano calcium carbonate A in anhydrous ethanol, ultrasonic treatment for 20-30 minutes to form a suspension, adding the stearic acid solution to the nano calcium carbonate suspension, stirring at 60-80°C for 10-20 minutes, cooling, centrifuging, washing and drying to obtain nano calcium carbonate B; dissolving a silane coupling agent in anhydrous ethanol, adding nano calcium carbonate B, heating to 50-70°C, stirring for 1-2 hours, washing and drying to obtain modified calcium carbonate.
[0012] As a preferred technical solution of the present invention, the concentration of the polyacrylic acid solution is 0.2-0.8%wt, and the mass ratio of polyacrylic acid, stearic acid, silane coupling agent and nano-calcium carbonate is 1-3:1-5:0.5-2:100.
[0013] As a preferred technical solution of the present invention, the heat stabilizer is a calcium zinc stabilizer.
[0014] Furthermore, the method for preparing the high-strength environmentally friendly plastic comprises the following steps:
[0015] (1) mixing and melting the modified PVC, PLA and compatibilizer at 140-150° C. for 10-15 minutes;
[0016] (2) Add filler and heat stabilizer and continue stirring and mixing at 160-180° C. for 10-20 minutes;
[0017] (3) Extruding the molten blend through a die and cooling it to solidify.
[0018] As a preferred technical solution of the present invention, the extrusion molding in step (3) uses a twin-screw extruder, sets the temperature gradient to 160-200°C, and controls the pressure during the extrusion process to be between 5-15MPa.
[0019] Beneficial effects of the present invention:
[0020] (1) The present invention blends chitosan grafted polyvinyl chloride with the environmentally friendly polymer polylactic acid, which not only improves the toughness of the material but also increases its biodegradability and antibacterial properties.
[0021] (2) The present invention uses polyacrylic acid, stearic acid and silane coupling agent to synergistically modify nano-calcium carbonate. Polyacrylic acid combines with calcium ions on the surface of calcium carbonate through chelation, thereby improving the dispersibility of nano-calcium carbonate in aqueous media and providing a better foundation for subsequent organic modifier coverage. Stearic acid reduces surface energy through physical adsorption, enhances dispersibility in organic solvents, and provides a hydrophobic surface environment for subsequent chemical bonding. The silane coupling agent forms a chemical bond between the inorganic nano-calcium carbonate and the organic polymer, effectively improving the dispersion and bonding of the nano-calcium carbonate in the polymer and increasing the strength of the material. DETAILED DESCRIPTION
[0022] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0023] In the following embodiments and comparative examples, the PVC was purchased from Yiwen Plastic Co., Ltd. with the product number DG-1000; PLA was purchased from Renfu Plastic Co., Ltd. with the brand number SZ3016; calcium zinc stabilizer was purchased from Jinheng Blue Ocean Technology Co., Ltd. with the product model JH918; nano-calcium carbonate was purchased from Korina New Materials Co., Ltd. with the product number 1, and silane coupling agent was purchased from Zhongjie Chemical Co., Ltd. with the product model 570; epoxy soybean oil was purchased from Deyitai New Materials Co., Ltd. with the single product number DYT-14; maleic anhydride grafted polyethylene was purchased from Kangjin Chemical Co., Ltd. with the product model 820, and polyacrylic acid was purchased from Huanju Technology Co., Ltd. with the product number PAA.
[0024] Example 1
[0025] A high-strength environmentally friendly plastic comprises the following raw materials in parts by weight: 25 parts by weight of modified PVC, 25 parts by weight of PLA, 5 parts by weight of a compatibilizer, 8 parts by weight of a filler and 3 parts by weight of a heat stabilizer.
[0026] The modified PVC is chitosan-grafted PVC, and the preparation method is: placing the PVC in a plasma reaction chamber for plasma treatment for 30 minutes to introduce carboxyl groups on the surface of the PVC; immersing the PVC in an N-hydroxysuccinimide aqueous solution for treatment for 1 hour to form an activated ester intermediate, immersing the activated ester intermediate in a chitosan solution for 6 hours for grafting, washing with deionized water, and then drying to obtain the chitosan-grafted PVC.
[0027] The plasma treatment uses 95% helium and 5% oxygen as barrier media, with a voltage of 5KV, a frequency of 40KHz, a duty cycle of 30%, and a modulation frequency of 100Hz; the concentration of the N-hydroxysuccinimide aqueous solution is 0.2M; the chitosan solution is a chitosan acetic acid solution, with an acetic acid concentration of 2% (V / V) and a chitosan concentration of 2% (m / m).
[0028] The compatibilizer is epoxidized soybean oil.
[0029] The filler is modified nano calcium carbonate, and the preparation method is as follows: adding nano calcium carbonate to a polyacrylic acid solution, stirring evenly and using ultrasonic-assisted dispersion treatment for 25 minutes, washing and drying to obtain nano calcium carbonate A; dissolving stearic acid in anhydrous ethanol to form a stearic acid solution, dispersing nano calcium carbonate A in anhydrous ethanol, ultrasonic treatment for 30 minutes to form a suspension, adding the stearic acid solution to the nano calcium carbonate suspension, stirring at 70°C for 20 minutes, cooling, centrifuging, washing, and drying to obtain nano calcium carbonate B; dissolving a silane coupling agent in anhydrous ethanol, adding nano calcium carbonate B, heating to 60°C, stirring for 1 hour, washing, and drying to obtain modified calcium carbonate.
[0030] The concentration of the polyacrylic acid solution is 0.5%wt, and the mass ratio of polyacrylic acid, stearic acid, silane coupling agent and nano-calcium carbonate is 2:4:1:100.
[0031] The heat stabilizer is a calcium zinc stabilizer.
[0032] The method for preparing a high-strength environmentally friendly plastic comprises the following steps:
[0033] (1) mixing and melting the modified PVC, PLA and compatibilizer at 150° C. with stirring for 15 minutes;
[0034] (2) Add filler and heat stabilizer and continue stirring and mixing at 180°C for 20 minutes;
[0035] (3) Extruding the molten blend through a die and cooling it to solidify.
[0036] As a preferred technical solution of the present invention, the extrusion molding in step (3) uses a twin-screw extruder, and the feed zone is set at 160°C, the compression zone is set at 170°C, the metering zone is set at 180°C, the mold zone is set at 190°C, and the pressure during extrusion is 10MPa.
[0037] Example 2
[0038] A high-strength environmentally friendly plastic comprises the following raw materials in parts by weight: 20 parts by weight of modified PVC, 30 parts by weight of PLA, 3 parts by weight of a compatibilizer, 5 parts by weight of a filler and 4 parts by weight of a heat stabilizer.
[0039] The modified PVC is chitosan-grafted PVC, and the preparation method is: placing the PVC in a plasma reaction chamber for plasma treatment for 30 minutes to introduce carboxyl groups on the surface of the PVC; immersing the PVC in an N-hydroxysuccinimide aqueous solution for treatment for 0.5 hours to form an activated ester intermediate, immersing the activated ester intermediate in a chitosan solution for 4 hours for grafting, washing with deionized water, and then drying to obtain the chitosan-grafted PVC.
[0040] The plasma treatment uses 99% helium and 1% oxygen as barrier media, with a voltage of 5KV, a frequency of 40KHz, a duty cycle of 30%, and a modulation frequency of 100Hz; the concentration of the N-hydroxysuccinimide aqueous solution is 0.1M; the chitosan solution is a chitosan acetic acid solution, with an acetic acid concentration of 1% (V / V) and a chitosan concentration of 1% (m / m).
[0041] The compatibilizer is maleic anhydride grafted polyethylene.
[0042] The filler is modified nano calcium carbonate, and the preparation method is as follows: adding nano calcium carbonate to a polyacrylic acid solution, stirring evenly and using ultrasonic assisted dispersion treatment for 20 minutes, washing and drying to obtain nano calcium carbonate A; dissolving stearic acid in anhydrous ethanol to form a stearic acid solution, then dispersing nano calcium carbonate A in anhydrous ethanol, ultrasonic treatment for 30 minutes to form a suspension, adding the stearic acid solution to the nano calcium carbonate suspension, stirring at 60°C for 20 minutes, cooling, centrifuging, washing, and drying to obtain nano calcium carbonate B; dissolving a silane coupling agent in anhydrous ethanol, adding nano calcium carbonate B, heating to 60°C, stirring for 0.5 hours, and then washing and drying to obtain modified calcium carbonate.
[0043] The concentration of the polyacrylic acid solution is 0.8%wt, and the mass ratio of polyacrylic acid, stearic acid, silane coupling agent and nano-calcium carbonate is 3:4:0.5:100.
[0044] The heat stabilizer is a calcium zinc stabilizer.
[0045] The method for preparing a high-strength environmentally friendly plastic comprises the following steps:
[0046] (1) mixing and melting the modified PVC, PLA and compatibilizer at 130° C. with stirring for 12 minutes;
[0047] (2) Add filler and heat stabilizer and continue stirring and mixing at 180°C for 10 minutes;
[0048] (3) Extruding the molten blend through a die and cooling it to solidify.
[0049] As a preferred technical solution of the present invention, the extrusion molding in step (3) uses a twin-screw extruder, and the feed zone is set at 170°C, the compression zone is set at 180°C, the metering zone is set at 190°C, the mold zone is set at 200°C, and the pressure during extrusion is 5MPa.
[0050] Comparative Example 1
[0051] A high-strength environmentally friendly plastic comprises the following raw materials in parts by weight: 25 parts by weight of PVC, 25 parts by weight of PLA, 5 parts by weight of a compatibilizer, 8 parts by weight of a filler and 3 parts by weight of a heat stabilizer.
[0052] The compatibilizer is epoxidized soybean oil.
[0053] The filler is modified nano calcium carbonate, and the preparation method is as follows: adding nano calcium carbonate to a polyacrylic acid solution, stirring evenly and using ultrasonic-assisted dispersion treatment for 25 minutes, washing and drying to obtain nano calcium carbonate A; dissolving stearic acid in anhydrous ethanol to form a stearic acid solution, dispersing nano calcium carbonate A in anhydrous ethanol, ultrasonic treatment for 30 minutes to form a suspension, adding the stearic acid solution to the nano calcium carbonate suspension, stirring at 70°C for 20 minutes, cooling, centrifuging, washing, and drying to obtain nano calcium carbonate B; dissolving a silane coupling agent in anhydrous ethanol, adding nano calcium carbonate B, heating to 60°C, stirring for 1 hour, washing, and drying to obtain modified calcium carbonate.
[0054] The concentration of the polyacrylic acid solution is 0.5%wt, and the mass ratio of polyacrylic acid, stearic acid, silane coupling agent and nano-calcium carbonate is 2:4:1:100.
[0055] The heat stabilizer is a calcium zinc stabilizer.
[0056] The method for preparing a high-strength environmentally friendly plastic comprises the following steps:
[0057] (1) stirring PVC, PLA and compatibilizer at 150° C. for 15 minutes to mix and melt;
[0058] (2) Add filler and heat stabilizer and continue stirring and mixing at 180°C for 20 minutes;
[0059] (3) Extruding the molten blend through a die and cooling it to solidify.
[0060] As a preferred technical solution of the present invention, the extrusion molding in step (3) uses a twin-screw extruder, and the feed zone is set at 160°C, the compression zone is set at 170°C, the metering zone is set at 180°C, the mold zone is set at 190°C, and the pressure during extrusion is 10MPa.
[0061] Comparative Example 2
[0062] A high-strength environmentally friendly plastic comprises the following raw materials in parts by weight: 25 parts by weight of modified PVC, 25 parts by weight of PLA, 5 parts by weight of a compatibilizer, 8 parts by weight of a filler and 3 parts by weight of a heat stabilizer.
[0063] The modified PVC is chitosan-grafted PVC, and the preparation method is: placing the PVC in a plasma reaction chamber for plasma treatment for 30 minutes to introduce carboxyl groups on the surface of the PVC; immersing the PVC in an N-hydroxysuccinimide aqueous solution for treatment for 1 hour to form an activated ester intermediate, immersing the activated ester intermediate in a chitosan solution for 6 hours for grafting, washing with deionized water, and then drying to obtain the chitosan-grafted PVC.
[0064] The plasma treatment uses 95% helium and 5% oxygen as barrier media, with a voltage of 5KV, a frequency of 40KHz, a duty cycle of 30%, and a modulation frequency of 100Hz; the concentration of the N-hydroxysuccinimide aqueous solution is 0.2M; the chitosan solution is a chitosan acetic acid solution, with an acetic acid concentration of 2% (V / V) and a chitosan concentration of 2% (m / m).
[0065] The compatibilizer is epoxidized soybean oil.
[0066] The filler is modified nano calcium carbonate, and the preparation method is as follows: dissolving stearic acid in anhydrous ethanol to form a stearic acid solution, dispersing nano calcium carbonate in anhydrous ethanol, ultrasonically treating for 30 minutes to form a suspension, adding the stearic acid solution to the nano calcium carbonate suspension, stirring at 70°C for 20 minutes, cooling, centrifuging, washing, and drying to obtain nano calcium carbonate A; dissolving a silane coupling agent in anhydrous ethanol, adding the nano calcium carbonate A, heating to 60°C, stirring for 1 hour, and then washing and drying to obtain modified calcium carbonate.
[0067] The mass ratio of the stearic acid, the silane coupling agent and the nano-calcium carbonate is 6:1:100.
[0068] The heat stabilizer is a calcium zinc stabilizer.
[0069] The method for preparing a high-strength environmentally friendly plastic comprises the following steps:
[0070] (1) mixing and melting the modified PVC, PLA and compatibilizer at 150° C. with stirring for 15 minutes;
[0071] (2) Add filler and heat stabilizer and continue stirring and mixing at 180°C for 20 minutes;
[0072] (3) Extruding the molten blend through a die and cooling it to solidify.
[0073] As a preferred technical solution of the present invention, the extrusion molding in step (3) uses a twin-screw extruder, and the feed zone is set at 160°C, the compression zone is set at 170°C, the metering zone is set at 180°C, the mold zone is set at 190°C, and the pressure during extrusion is 10MPa.
[0074] Comparative Example 3
[0075] A high-strength environmentally friendly plastic comprises the following raw materials in parts by weight: 25 parts by weight of modified PVC, 25 parts by weight of PLA, 5 parts by weight of a compatibilizer, 8 parts by weight of a filler and 3 parts by weight of a heat stabilizer.
[0076] The modified PVC is chitosan-grafted PVC, and the preparation method is: placing the PVC in a plasma reaction chamber for plasma treatment for 30 minutes to introduce carboxyl groups on the surface of the PVC; immersing the PVC in an N-hydroxysuccinimide aqueous solution for treatment for 1 hour to form an activated ester intermediate, immersing the activated ester intermediate in a chitosan solution for 6 hours for grafting, washing with deionized water, and then drying to obtain the chitosan-grafted PVC.
[0077] The plasma treatment uses 95% helium and 5% oxygen as barrier media, with a voltage of 5KV, a frequency of 40KHz, a duty cycle of 30%, and a modulation frequency of 100Hz; the concentration of the N-hydroxysuccinimide aqueous solution is 0.2M; the chitosan solution is a chitosan acetic acid solution, with an acetic acid concentration of 2% (V / V) and a chitosan concentration of 2% (m / m).
[0078] The compatibilizer is epoxidized soybean oil.
[0079] The filler is modified nano calcium carbonate, and the preparation method is as follows: adding nano calcium carbonate to polyacrylic acid solution, stirring evenly, using ultrasonic assisted dispersion treatment for 25 minutes, washing and drying to obtain nano calcium carbonate A; dissolving silane coupling agent in anhydrous ethanol, adding nano calcium carbonate A, heating to 60°C, stirring for 1 hour, washing and drying to obtain modified calcium carbonate.
[0080] The concentration of the polyacrylic acid solution is 0.5%wt, and the mass ratio of polyacrylic acid, silane coupling agent and nano-calcium carbonate is 2:5:100.
[0081] The heat stabilizer is a calcium zinc stabilizer.
[0082] The method for preparing a high-strength environmentally friendly plastic comprises the following steps:
[0083] (1) mixing and melting the modified PVC, PLA and compatibilizer at 150° C. with stirring for 15 minutes;
[0084] (2) Add filler and heat stabilizer and continue stirring and mixing at 180°C for 20 minutes;
[0085] (3) Extruding the molten blend through a die and cooling it to solidify.
[0086] As a preferred technical solution of the present invention, the extrusion molding in step (3) uses a twin-screw extruder, and the feed zone is set at 160°C, the compression zone is set at 170°C, the metering zone is set at 180°C, the mold zone is set at 190°C, and the pressure during extrusion is 10MPa.
[0087] Comparative Example 4
[0088] A high-strength environmentally friendly plastic comprises the following raw materials in parts by weight: 25 parts by weight of modified PVC, 25 parts by weight of PLA, 5 parts by weight of a compatibilizer, 8 parts by weight of a filler and 3 parts by weight of a heat stabilizer.
[0089] The modified PVC is chitosan-grafted PVC, and the preparation method is: placing the PVC in a plasma reaction chamber for plasma treatment for 30 minutes to introduce carboxyl groups on the surface of the PVC; immersing the PVC in an N-hydroxysuccinimide aqueous solution for treatment for 1 hour to form an activated ester intermediate, immersing the activated ester intermediate in a chitosan solution for 6 hours for grafting, washing with deionized water, and then drying to obtain the chitosan-grafted PVC.
[0090] The plasma treatment uses 95% helium and 5% oxygen as barrier media, with a voltage of 5KV, a frequency of 40KHz, a duty cycle of 30%, and a modulation frequency of 100Hz; the concentration of the N-hydroxysuccinimide aqueous solution is 0.2M; the chitosan solution is a chitosan acetic acid solution, with an acetic acid concentration of 2% (V / V) and a chitosan concentration of 2% (m / m).
[0091] The compatibilizer is epoxidized soybean oil.
[0092] The filler is modified nano calcium carbonate, and the preparation method is as follows: adding nano calcium carbonate to a polyacrylic acid solution, stirring evenly, using ultrasonic-assisted dispersion treatment for 25 minutes, washing and drying to obtain nano calcium carbonate A; dissolving stearic acid in anhydrous ethanol to form a stearic acid solution, then dispersing nano calcium carbonate A in anhydrous ethanol, ultrasonic treatment for 30 minutes to form a suspension, adding the stearic acid solution to the nano calcium carbonate suspension, stirring at 70°C for 20 minutes, cooling, centrifuging, washing, and drying to obtain the modified nano calcium carbonate.
[0093] The concentration of the polyacrylic acid solution is 0.5%wt, and the mass ratio of polyacrylic acid, stearic acid and nano-calcium carbonate is 3:4:100.
[0094] The heat stabilizer is a calcium zinc stabilizer.
[0095] The method for preparing a high-strength environmentally friendly plastic comprises the following steps:
[0096] (1) mixing and melting the modified PVC, PLA and compatibilizer at 150° C. with stirring for 15 minutes;
[0097] (2) Add filler and heat stabilizer and continue stirring and mixing at 180°C for 20 minutes;
[0098] (3) Extruding the molten blend through a die and cooling it to solidify.
[0099] As a preferred technical solution of the present invention, the extrusion molding in step (3) uses a twin-screw extruder, and the feed zone is set at 160°C, the compression zone is set at 170°C, the metering zone is set at 180°C, the mold zone is set at 190°C, and the pressure during extrusion is 10MPa.
[0100] Comparative Example 5
[0101] A high-strength environmentally friendly plastic comprises the following raw materials in parts by weight: 25 parts by weight of modified PVC, 25 parts by weight of PLA, 5 parts by weight of a compatibilizer, 8 parts by weight of a filler and 3 parts by weight of a heat stabilizer.
[0102] The modified PVC is chitosan-grafted PVC, and the preparation method is: placing the PVC in a plasma reaction chamber for plasma treatment for 30 minutes to introduce carboxyl groups on the surface of the PVC; immersing the PVC in an N-hydroxysuccinimide aqueous solution for treatment for 1 hour to form an activated ester intermediate, immersing the activated ester intermediate in a chitosan solution for 6 hours for grafting, washing with deionized water, and then drying to obtain the chitosan-grafted PVC.
[0103] The plasma treatment uses 95% helium and 5% oxygen as barrier media, with a voltage of 5KV, a frequency of 40KHz, a duty cycle of 30%, and a modulation frequency of 100Hz; the concentration of the N-hydroxysuccinimide aqueous solution is 0.2M; the chitosan solution is a chitosan acetic acid solution, with an acetic acid concentration of 2% (V / V) and a chitosan concentration of 2% (m / m).
[0104] The compatibilizer is epoxidized soybean oil.
[0105] The filler is nano calcium carbonate.
[0106] The heat stabilizer is a calcium zinc stabilizer.
[0107] The method for preparing a high-strength environmentally friendly plastic comprises the following steps:
[0108] (1) mixing and melting the modified PVC, PLA and compatibilizer at 150° C. with stirring for 15 minutes;
[0109] (2) Add filler and heat stabilizer and continue stirring and mixing at 180°C for 20 minutes;
[0110] (3) Extruding the molten blend through a die and cooling it to solidify.
[0111] As a preferred technical solution of the present invention, the extrusion molding in step (3) uses a twin-screw extruder, setting the feed zone at 160°C, the compression zone at 170°C, the metering zone at 180°C, the mold zone at 190°C, and the pressure during extrusion is 10MPa
[0112] Performance Testing:
[0113] Impact strength test: The high-strength environmentally friendly plastics in Examples 1-2 and Comparative Examples 1-5 were tested according to GB / T1043.1-2008 standard. The sample size was 80mmx10mmx4mm. The impact tester used was WKT-LC2000. The unit was kJ / m 2 .
[0114] Toughness test: The high-strength environmentally friendly plastics in Examples 1-2 and Comparative Examples 1-5 were tested for flexural strength according to GB / T1041-2008 standard, with the unit being Mpa.
[0115] Antibacterial performance: The high-strength environmentally friendly plastics in Examples 1-2 and Comparative Example 1 were made into test pieces (1 cm × 1 cm), and a bacterial suspension of Staphylococcus aureus was prepared according to the method in Appendix C5 of GB15979-2002; 20 ml PBS and 5 ml bacterial suspension were mixed and added to the test piece, so that the concentration of the bacterial suspension in PBS was 9 × 10 4 cfu / ml, shake at 300r / min for 1h, take out the sample, add 20ml PBS and continue shaking for 1h to prepare the sample solution, take 0.5ml of the shaken sample solution, inoculate it into the culture dish by the agar inoculation method, and count the colonies. Repeat the test three times and take the average value in cfu / ml.
[0116] Biodegradation: The high-strength environmentally friendly plastics in Examples 1-25 and Comparative Example 1 were subjected to the soil landfill test method in accordance with GB / T19275-2003 "Evaluation of the Potential Biodegradability and Disintegration of Materials under the Action of Specific Microorganisms". The landfill time was 90 days. The biodegradability of the materials was evaluated by the average percentage (%) of mass change. The higher the value, the better the biodegradability.
[0117] The test results are shown in the table:
[0118]
[0119]
[0120] The test results show that the present invention not only improves the toughness of the material by blending PLA with chitosan-grafted PVC, but also increases its biodegradability and antibacterial properties; the impact strength of the material is increased by adding filler nano calcium carbonate, and the nano calcium carbonate is modified by polyacrylic acid, stearic acid and silane coupling agent, which effectively improves the dispersion and combination of inorganic calcium carbonate in the polymer, further increasing the strength of the material.
[0121] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any indirect modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A high-strength environmentally friendly plastic, characterized in that: The invention comprises the following raw materials in parts by weight: 20-30 parts by weight of modified PVC, 20-30 parts by weight of PLA, 2.5-10 parts by weight of a compatibilizer, 6-10 parts by weight of a filler and 3-4 parts by weight of a heat stabilizer.
2. The high-strength environmentally friendly plastic according to claim 1, characterized in that: The modified PVC is chitosan-grafted PVC, and the preparation method is: placing the PVC in a plasma reaction chamber for plasma treatment for 20-40 minutes to introduce carboxyl groups on the surface of the PVC; immersing the PVC in an N-hydroxysuccinimide aqueous solution for treatment for 0.5-1 hour to form an activated ester intermediate, immersing the activated ester intermediate in a chitosan solution for 2-8 hours for grafting, washing with deionized water, and drying to obtain the chitosan-grafted PVC.
3. The high-strength environmentally friendly plastic according to claim 2, characterized in that: The plasma treatment uses 95%-99% helium and 1%-5% oxygen as barrier media, with a voltage of 3-8KV, a frequency of 30-50KHz, a duty cycle of 25%-55%, and a modulation frequency of 80-120Hz; the concentration of the N-hydroxysuccinimide aqueous solution is 0.1-0.2M; the chitosan solution is a chitosan acetic acid solution, the acetic acid concentration is 1-2% (V / V), and the chitosan concentration is 1-2% (m / m).
4. The high-strength environmentally friendly plastic according to claim 1, characterized in that: The compatibilizer is any one of epoxy soybean oil, maleic anhydride grafted polyethylene and maleic anhydride grafted polypropylene.
5. The high-strength environmentally friendly plastic according to claim 1, characterized in that: The filler is modified nano calcium carbonate, and the preparation method is as follows: adding nano calcium carbonate to a polyacrylic acid solution, stirring evenly and using ultrasonic assisted dispersion treatment for 20-30 minutes, washing and drying to obtain nano calcium carbonate A; dissolving stearic acid in anhydrous ethanol to form a stearic acid solution, dispersing nano calcium carbonate A in anhydrous ethanol, ultrasonic treatment for 20-30 minutes to form a suspension, adding the stearic acid solution to the nano calcium carbonate suspension, stirring at 60-80°C for 10-20 minutes, cooling, centrifuging, washing, and drying to obtain nano calcium carbonate B; dissolving a silane coupling agent in anhydrous ethanol, adding nano calcium carbonate B, heating to 50-70°C, stirring for 1-2 hours, washing, and drying to obtain modified calcium carbonate.
6. The high-strength environmentally friendly plastic according to claim 5, characterized in that: The concentration of the polyacrylic acid solution is 0.2-0.8%wt, and the mass ratio of polyacrylic acid, stearic acid, silane coupling agent and nano calcium carbonate is 1-3:1-5:0.5-2:
100.
7. The high-strength environmentally friendly plastic according to claim 1, characterized in that: The heat stabilizer is a calcium zinc stabilizer.
8. A method for preparing a high-strength environmentally friendly plastic according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) mixing and melting the modified PVC, PLA and compatibilizer at 140-150° C. for 10-15 minutes; (2) Add filler and heat stabilizer and continue stirring and mixing at 160-180° C. for 10-20 minutes; (3) Extruding the molten blend through a die and cooling it to solidify.
9. The method for preparing a high-strength environmentally friendly plastic according to claim 8, characterized in that: The extrusion molding in step (3) uses a twin-screw extruder, sets the temperature gradient to 160-200° C., and controls the pressure during the extrusion process to be between 5-15 MPa.
Citation Information
Patent Citations
Environment-friendly polyvinyl chloride resin composition and preparation method thereof
CN103571105A
Heparinized PVC (polyvinyl chloride) material, preparation method thereof and application of heparinized PVC material as medical instrument
CN114106493A